Co‐Culture of Human Primary Hepatocytes and Nonparenchymal Liver Cells in the Emulate® Liver‐Chip for the Study of Drug‐Induced Liver Injury. Issue 7 (5th July 2022) - Shi, Qiang; Arefin, Ayesha; Ren, Lijun; Papineau, Katy S.; Barnette, Dustyn A.; Schnackenberg, Laura K.; Hawes, Jessica J.; Avigan, Mark; Mendrick, Donna L.; Ewart, Lorna; Ronxhi, Janey
Abstract: Drug‐induced liver injury (DILI) is a significant public health issue, but standard animal tests and clinical trials sometimes fail to predict DILI due to species differences and the relatively low number of human subjects involved in preapproval studies of a new drug, respectively. In vitro models have long been used to aid DILI prediction, with primary human hepatocytes (PHHs) being generally considered the gold standard. However, despite many efforts and decades of work, traditional culture methods have been unsuccessful in either fully preserving essential liver functions after isolation of PHHs or in emulating interactions between PHHs and hepatic nonparenchymal cells (NPCs), both of which are essential for the development of DILI under in vivo conditions. Recently, various liver‐on‐a‐chip (Liver‐Chip) systems have been developed to co‐culture hepatocytes and NPCs in a three‐dimensional environment on microfluidic channels, enabling better maintenance of primary liver cells and thus improved DILI prediction. The Emulate® Liver‐Chip is a commercially available system that can recapitulate some in vivo DILI responses associated with certain compounds whose liver safety profile cannot be accurately evaluated using conventional approaches involving PHHs or animal models due to a lack of innate immune responses or species‐dependent toxicity, respectively. Here, we describe detailed procedures for the use of Emulate® Liver‐Chips for co‐culturing PHHs and NPCs for the purpose of DILI evaluation. First, we describe the procedures for preparing the Liver‐Chip. We then outline the steps needed for sequential seeding of PHHs and NPCs in the prepared Liver‐Chips. Lastly, we provide a protocol for utilizing cells maintained in perfusion culture in the Liver‐Chips to evaluate DILI, using acetaminophen as an example. In all, use of this system and the procedures described here allow better preservation of the functions of human primary liver cells, resulting in an improved in vitro model for DILI assessment. © 2022 Wiley Periodicals LLC. This article has been contributed to by US Government employees and their work is in the public domain in the USA. Basic Protocol 1 : Liver‐Chip preparation Basic Protocol 2 : Seeding primary human hepatocytes and nonparenchymal cells on Liver‐Chips Basic Protocol 3 : Perfusion culture for the study of acetaminophen‐induced liver injury